Pengaruh Penggunaan Konseling Kelompok Trait and Factor Terhadap Ketepatan Pemilihan Jurusan Siswa - M. Fahli Zatrahadi; Neviyarni Neviyarni; Yeni Karneli; Netrawati Netrawati (Universitas Lampung, 2021)
The choice of majors at school is part of career exploration as preparation for entering the world of professional work. However, choosing a major can be confusing for students. This study aims to determine the effect of using trait and factor group counseling on the accuracy of majors selection. The research uses a quantitative approach with the correlational method. The sample in this study were 91 students of class XII who had made the selection of majors. Data were analyzed using regression analysis with the help of SPSS 25 for Windows. The results show that there is no significant effect between the use of trait and factor group counseling on the accuracy of majors selection.Keywords: accuracy of majors selection, group counseling, trait and factor approach DOI: http://dx.doi.org/10.23960/jiip.v3i2.23271